EVALUASI PENGELOLAAN SAMPAH RUMAH SAKIT PUSAT ANGKATAN DARAT GATOT SOEBROTO - Paramita, Nadia (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2007)
Activity in a hospital producing organic and inorganic solid waste.the characteristics of  the solid waste are devided into domestic and medical which have to be destroyed immidiatly, so they wont coused any environmental problems. One way to prevent the danger coused by  those  waste  is  using  the  right hospital  waste  management  from  the  source  until  the destruction parts. In waste management, it is important separate between medical and non medical  waste  from  the  source  than  continue  with  the right  storage,  and  transportation steps.  To  destroy  medical  waste,  controlled  air  incinerator  with multychamber  is recommended  incinerator  technology.  With  two  steps  of  burning  processes  will make complete  combustion.  Experiment  of  medical  waste  incinerator  with  abaout  5 m3 capacitiesshows  the  batch  combustion  system  at  800-1600  ºC  temperature.  Using that incinerator, the volume of this medical solid waste can be reduceduntil ± 67 % and mass reduction until 70-80 %.